Extracellular Vesicles as Inflammatory Drivers in NAFLD - Srinivas, Akshatha N.; Suresh, Diwakar; Santhekadur, Prasanna K.; Suvarna, Deepak; Kumar, Divya P. (Frontiers in Immunology, 2021)
Non-alcoholic fatty liver disease (NAFLD) is a highly prevalent chronic liver disease in most parts of the world affecting one-third of the western population and a growing cause for end-stage liver diseases such as hepatocellular carcinoma (HCC). Majorly driven by obesity and diabetes mellitus, NAFLD is more of a multifactorial disease affected by extra-hepatic organ crosstalk. Non-alcoholic fatty liver (NAFL) progressed to non-alcoholic steatohepatitis (NASH) predisposes multiple complications such as fibrosis, cirrhosis, and HCC. Although the complete pathogenic mechanisms of this disease are not understood, inflammation is considered as a key driver to the onset of NASH. Lipotoxicity, inflammatory cytokines, chemokines, and intestinal dysbiosis trigger both hepatic and systemic inflammatory cascades simultaneously activating immune responses. Over a few years, extracellular vesicles studied extensively concerning the pathobiology of NAFLD indicated it as a key modulator in the setting of immune-mediated inflammation. Exosomes and microvesicles, the two main types of extracellular vesicles are secreted by an array of most mammalian cells, which are involved mainly in cell-cell communication that are unique to cell type. Various bioactive cargoes containing extracellular vesicles derived from both hepatic and extrahepatic milieu showed critical implications in driving steatosis to NASH reaffirming inflammation as the primary contributor to the whole process. In this mini-review, we provide brief insights into the inflammatory mediators of NASH with special emphasis on extracellular vesicles that acts as drivers of inflammation in NAFLD.